Aphelinus asychis (Hymenoptera, Aphelinidae) —перспективный энтомофаг в условиях закрытого грунта - Зерова, М.Д.; Крыжановская, Т.В. (Вестник зоологии, 1984)
Aphelinus asychis (Hymenoptera, Aphelinidae) —a Promising Pest Control Agent Under Covered Soil Conditions. Zerova M. D., Kryzhanovskaya T. V.— Vestn. zool., 1984, No. 3. An aphid predator, Aphelinus asychus Walk. for the first time found in the Ukraine, is suggested to be a promising agent of aphids control in greenhouses. A redescription of female and male is given.